Electrostatic generator enhancements for powering IoT nodes via efficient energy management - Zibo Wu; Zeyuan Cao; Junchi Teng; Rong Ding; Jiani Xu; Xiongying Ye (Microsystems & Nanoengineering, 2024)
Abstract Electrostatic generators show great potential for powering widely distributed electronic devices in Internet of Things (IoT) applications. However, a critical issue limiting such generators is their high impedance mismatch when coupled to electronics, which results in very low energy utilization efficiency. Here, we present a high-performance energy management unit (EMU) based on a spark-switch tube and a buck converter with an RF inductor. By optimizing the elements and parameters of the EMU, a maximum direct current output power of 79.2 mW m-2 rps-1 was reached for a rotary electret generator with the EMU, achieving 1.2 times greater power output than without the EMU. Furthermore, the maximum power of the contact-separated triboelectric nanogenerator with an EMU is 1.5 times that without the EMU. This excellent performance is attributed to the various optimizations, including utilizing an ultralow-loss spark-switch tube with a proper breakdown voltage, adding a matched input capacitor to enhance available charge, and incorporating an RF inductor to facilitate the high-speed energy transfer process. Based on this extremely efficient EMU, a compact self-powered wireless temperature sensor node was demonstrated to acquire and transmit data every 3.5 s under a slight wind speed of 0.5 m/s. This work greatly promotes the utilization of electrostatic nanogenerators in practical applications, particularly in IoT nodes.